2023
DOI: 10.1136/bmjopen-2023-073833
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypertension service availability in some primary health centres in Nigeria: a mixed-methods study

Oluseyi Adejumo,
Olorunfemi Ogundele,
Manmak Mamven
et al.

Abstract: ObjectiveStrengthening primary health centre (PHC) systems is a potentially effective strategy to reduce the burden of non-communicable diseases in Nigeria, a low/middle-income country with limited resources. The aim of this study was to assess hypertension service availability in some PHCs in Nigeria and seek recommendations that could facilitate improved services from PHC workers.DesignExplanatory sequential mixed-methods study.SettingsPHCs in the six geopolitical zones and Federal Capital City of Nigeria.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Research conducted in a tertiary hospital in Owo town, Ondo state, reported that 97.7% of hypertensive outpatients stated expensive cost of treatment as the major reason for lack of adherence to antihypertensive treatment [31]. This also places a significant strain on health care facilities as the majority of health facilities are in unfavorable conditions due to lack of healthcare personnel and resources, and the high levels of poverty in our community, all these can prevent proper intervention for this population and also increase mortality [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in a tertiary hospital in Owo town, Ondo state, reported that 97.7% of hypertensive outpatients stated expensive cost of treatment as the major reason for lack of adherence to antihypertensive treatment [31]. This also places a significant strain on health care facilities as the majority of health facilities are in unfavorable conditions due to lack of healthcare personnel and resources, and the high levels of poverty in our community, all these can prevent proper intervention for this population and also increase mortality [32,33].…”
Section: Introductionmentioning
confidence: 99%